2001
DOI: 10.1177/002221940103400504
|View full text |Cite
|
Sign up to set email alerts
|

Does Strategy Knowledge Influence Working Memory in Children with Mathematical Disabilities?

Abstract: This study investigated the relationship between working memory (WM), declarative strategy knowledge, and math achievement in children with and without mathematical disabilities (MD). Experiment 1 examined the relationship between strategy knowledge, verbal WM, and visual-spatial WM in children with MD as a function of initial, gain, and maintenance conditions. The results showed that after partialing the influence of reading, stable strategy choices rather than specific strategy knowledge was related to verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 33 publications
(46 reference statements)
4
68
0
5
Order By: Relevance
“…Very few studies tested math ability-matched control children (Andersson and Lyxell, 2007;Keeler and Swanson, 2001;McLean and Hitch, 1999;Swanson, 1993;Swanson and Sachse-Lee, 2001). One of these studies reported that MLD performed worse than age-matched controls but better than ability-matched controls in verbal/visual WM (Swanson, 1993).…”
Section: Studies With Ability-matched Young Controls and Interventionmentioning
confidence: 99%
“…Very few studies tested math ability-matched control children (Andersson and Lyxell, 2007;Keeler and Swanson, 2001;McLean and Hitch, 1999;Swanson, 1993;Swanson and Sachse-Lee, 2001). One of these studies reported that MLD performed worse than age-matched controls but better than ability-matched controls in verbal/visual WM (Swanson, 1993).…”
Section: Studies With Ability-matched Young Controls and Interventionmentioning
confidence: 99%
“…Em um estudo brasileiro, Corso (2008) Outros pesquisadores acreditam que os problemas principais referentes ao executivo central dizem respeito à recuperação de informação da memória de longo prazo e à coordenação de desempenho de duas operações independentes, do tipo armazenar e processar informação simultaneamente (GEARY, 2004;KELLER;SWANSON, 2001).…”
Section: Prejuízos Na Memória De Trabalho: Gerais Ou Específicos?unclassified
“…For students there is often a perception that the expectations about mathematics skills are unrealistic, for example, in the Anxiety can also adversely impact upon the cognitive skills used during mathematical tasks, such as working memory (Ashcraft, Kirk, & Hopko, 1998). Working memory is a significant predictor of mathematical achievement (Keeler & Swanson, 2001); therefore, anxiety can act to reduce the capacity of one of the key sub-skills needed to succeed in this domain. Hadfield and McNeil (1994) have proposed a model of maths anxiety, which centres on three main factors: environmental, intellectual and personality variables.…”
Section: Introductionmentioning
confidence: 99%